Role of Cultural Graphics Strategies in Shaping Urban Identity: A Quantitative Study of User Perception in Qinzhou City - Zhang, Chunli; Wardi, Rainal Hidayat Bin; Ghazali, Rusmawati Binti (Journal of Ecohumanism, 2025)
The paper attempts to investigate the role that street art, murals, and other signage play in forming and defining urban identity through research on Qinzhou City, Guangxi, China. The study employs a quantitative approach and structural equation modeling (SEM-PLS), which examines the interaction among cultural identity, social identity, media consumption, personal values, and beliefs and how these interact to affect cultural perception. Results of the study indicate that both cultural identity and social identity have significant influences on cultural perception, with media consumption and personal values and beliefs acting as critical mediators. Cultural Identity fosters the connection of personal beliefs strongly, whereas Social Identity tends to drive media consumption behaviors that affect cultural understanding. The study provides theoretical and practical implications for urban planners, policymakers, and media strategists in exploiting cultural graphics to improve urban cultural environments. Despite its limitations in geographical scope, the study provides useful insights into the intersection of cultural and social dynamics and offers a model for urban cultural policy and development strategies.